LONG OF HEMODIALYSIS THERAPY WITH QUALITY LIFE PATIENT FAILS OF KIDNEY CHRONIC IN RS GATOEL MOJOKERTO: STUDY CROSS-SECTIONAL - arif wicaksono; muhammad sajidin (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2017)
Hemodialysis therapy of patients with chronic kidney disease can changes the patients physically, psychological, social and economics because they have to deal with it for the rest of their life. This can affect the quality of life of the patients because of the long-term of hemodialysis therapy, this is one of the factors that affect the quality of life of the patients with chronic kidney disease. Quality of life is focused on the assessment of the individual against conditions acceptance. Each individual takes different phases to accept the condition. The purposes of the study were to determine if the relationship between the duration of hemodialysis and quality of life of the patients with chronic kidney disease at Gatoel Hospital Mojokerto. This research used cross-sectional design. The patient's population with chronic kidney disease undergoing hemodialysis is 150 people. The research sample is drawn using sampling techniques with the type of nonprobability purposive sampling with 130 people as a sample. Data obtained from questionnaires KDQoL 36. The result using Spearman rho test using SPSS V.16 shows p < Î± (0,006 < 0,05). H0 rejected, this means that there is a relationship between the duration of hemodialysis and quality of life with chronic kidney disease at Gatoel Hospital Mojokerto. The quality of life of the patients fluctuated based on the stage adaptation of the hemodialysis and disease. However, most patients with the duration of hemodialysis for more than 12 months had a sufficient quality of life and their therapy are already familiar with the symptoms and complications, but there are other factors that affect the quality of life such as gender, marital status, and education level. Patients are also expected to cooperate in what to do and not to do to improve the quality of life of the patients.